The Antecedents and Consequences of Ecotourist Place Attachment - ., Marso; Gunawan, S (KnE Social Sciences, 2018)
This study aims to test some antecedents and consequences of place attachment in a structural model. Ecotourism destination image and perceived value are specified as the antecedents of place attachment, while satisfaction and intention loyalty act as its consequences. This model was tested on 218 visitors to Tanjung Puting National Park (TPNP) in Central Kalimantan, Indonesia. TPNP is the largest rehabilitation centre for orangutans and is promoted as one of the ecotourism destinations in Indonesia. SmartPLS 3.0 Professional was employed to assess the convergent and discriminant validity of the measurement items for each construct and structural model. The findings confirmed seven out of ten hypotheses. Theoretically, this study’s findings contributed to expanding the tourist loyalty model; in terms of managerial implications, this study can be utilized in the marketing of ecotourism destinations. Keywords: ecotourism destination image, perceived value, place attachment, satisfaction, intention loyalty